TNF-α-mediated epithelial-to-mesenchymal transition regulates expression of immune checkpoint molecules in hepatocellular carcinoma - Shrestha, Ritu (Mol Med Rep, 2020)
Hepatocellular carcinoma (HCC) is the fastest growing cause of cancer-related deaths globally. Epithelial-to-mesenchymal transition (EMT) is a cellular process that confers HCC tumor cells with the ability to evade the immune system. Immune escape in most tumors, including HCC, is controlled by immune checkpoint molecules. The aim of the present study was to investigate the association between EMT and immune checkpoint in HCC, and identify novel therapeutic targets for HCC. An in vitro model of reversible EMT was utilized based on cytokine tumor necrosis factor (TNF)-α treatment of HCC cell lines Hep3B and PLC/PRF/5. Hep3B and PLC/PRF/5 cells were treated with TNF-α, and the EMT status and the expression of immune checkpoint molecules was assessed by reverse transcription-quantitative PCR, western blotting and immunofluorescence. To confirm an association between EMT and immune modulators, cells were exposed to culture medium with TNF-α for 3 days to induce EMT, following which a reversal assay was performed. The expression of immune modulators and mesenchymal-to-epithelial transition (MET) status was investigated upon reversal of EMT. Furthermore, SurvExpress, a web-based platform was utilized to analyze survival and recurrence in a dataset of patients with HCC. TNF-α treatment for 3 days induced EMT in Hep3B and PLC/PRF/5 cells, as demonstrated by the downregulation of epithelial markers along with upregulation in mesenchymal markers. An EMT reversal assay was able to induce MET by increasing epithelial markers and decreasing mesenchymal markers. TNF-α-induced EMT led to the upregulation of immune modulators, including programmed death receptor ligand (PD-L)1, PD-L2, CD73 and B7-H3. In contrast, reversal of EMT suppressed the expression of PD-L1, PD-L2, CD73 and B7-H3. In addition, high expression of TNF-α and PD-L1 in 422 patients with HCC was associated with poor overall survival. The coordinate expression of TNF-α with PD-L2 in this patient cohort was associated with increased HCC recurrence. In conclusion, the present study demonstrated a close association between immune modulator expression and EMT induction/reversal driven by TNF-α.